AKUNTABILITAS PENYELENGGARAAN ASAS TUGAS PEMBANTUAN DI DESA SENDURO KECAMATAN SENDURO KABUPATEN LUMAJANG - Wibowo, Angga Trie Sugiarto (Universitas 17 Agustus 1945 Surabaya, 2016)
The principles co-administration is effort of the central government as funder with contribute task to the local government for improve effective and efficient doimplementation government, development management and public service. Thestudy aims to understand and analyze about process and influence effectaccountability principles co-administration in the local government Senduro Subdistrict Lumajang Regency. This study is a descriptive research with qualitativeresearch method. The method collecting data in this study was used interviewsand documentation. The result of this research showing that: 1) the processimplementation of accountability principles co-administration in the SenduroVillage Senduro Sub district Lumajang Regency was doing a good. In this means,need to enhanced and maintained. 2) The factors that influence it, namely thetime, cost, effectiveness, externalities. Keywords : Accountability, Co-administration, Local Government